New Extrapolation Formula (Al-karamy3) to improve the results of numerical integrals - Al-Karamy, Nada .A.M.; Hilal, Rana Hasan; jabir, Sundud najah (International Journal of Psychosocial Rehabilitation, 2020)
The main objective of this research is to find a new Extrapolation formula derivative to produce results for numerical integrations. By using the Regardson acceleration as well as utilizing the rest of the excitation lines and the Mcluren series of the Pocket function to improve the accuracy of the results obtained from the Regardson acceleration application.